2009
DOI: 10.1007/s11242-009-9416-z
|View full text |Cite
|
Sign up to set email alerts
|

Leak-off During Placement of Cr(III)-Partially Hydrolyzed Polyacrylamide Gelling Solution in Fractured Porous Media

Abstract: During waterflooding of a fractured formation, water may channel through the fracture or interconnected network of fractures, leaving a large portion of oil bearing rock unswept. One remedial practice is injection of a gelling solution into the fracture. Such placement of a gelling mixture (referred as gelant) is associated with leak-off from the face of the fracture into the adjoining matrix. As the gelant gets more crosslinked, the gelant encounters more resistance in flowing into the porous matrix. This art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…As shown in Figures and , with the reduction of the matrix permeability from 100 to 10 mD, the injected pore volume of the gelant decreased from 0.51 to 0.44 PV and the injected fracture volume was reduced from 1.76 to 1.18 FV as the pressure gradient reached a stable value, i.e., when the fracture widths of cores are similar, to achieve a stable injection pressure, a relatively small volume of the gelant is required to be injected into a fractured core with relatively low matrix permeability. It is because that the degree of the gelant diffusion or penetration from fracture into matrix decreased with the reduction of the matrix permeability, and it results in a reduction of the cumulative lost volume of the gelant . The effect of the matrix permeability on the loss degree of the gelant was discussed in the section .…”
Section: Results and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As shown in Figures and , with the reduction of the matrix permeability from 100 to 10 mD, the injected pore volume of the gelant decreased from 0.51 to 0.44 PV and the injected fracture volume was reduced from 1.76 to 1.18 FV as the pressure gradient reached a stable value, i.e., when the fracture widths of cores are similar, to achieve a stable injection pressure, a relatively small volume of the gelant is required to be injected into a fractured core with relatively low matrix permeability. It is because that the degree of the gelant diffusion or penetration from fracture into matrix decreased with the reduction of the matrix permeability, and it results in a reduction of the cumulative lost volume of the gelant . The effect of the matrix permeability on the loss degree of the gelant was discussed in the section .…”
Section: Results and Discussionsupporting
confidence: 90%
“…It is because that the degree of the gelant diffusion or penetration from fracture into matrix decreased with the reduction of the matrix permeability, and it results in a reduction of the cumulative lost volume of the gelant. 20 The effect of the matrix permeability on the loss degree of the gelant was discussed in the section 3.1.4.…”
Section: Gelant and Gel Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the flow characteristics of the HPAM/Cr 3+ system in a fracture channeling path are different from those in porous medium channeling path; thus, the research results of the transportation of the HPAM/Cr 3+ system in the conventional reservoir cannot be applied to a fractured tight reservoir. However, there are only a few studies on the transportation of the HPAM/Cr 3+ system in natural microfractures, and almost all of those are focused on the loss of the gelling solution from the fracture face into the adjoining matrix. Thus, it is necessary to study the influence of the M w of the HPAM on the transportation of the HPAM/Cr 3+ system in microfractures to improve the application effect of the HPAM/Cr 3+ system in a fractured tight reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Junjian et al studied the filtrate behavior and water shutoff performance of a certain gel in fractured media (11). Ganguly et al reported that the gel plugging agent could cement the fracture surface during the gelling of the plugging agent, thus enhancing its fracture plugging performance (12). So far, the effect of the leak off degree of the plugging agent components on its gelling effect and plugging performance has not been characterized quantitatively.…”
Section: Introductionmentioning
confidence: 99%